Family planning practice among married Orang Asli women in Sepang district and its associated factors - Hassan, Hasneezah; Abdul Manaf, Rosliza; Ismail, Suriani (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Family planning allows couples to have their desired number of children and optimum birth spacing. While the contraceptive prevalence rate (CPR) in Malaysia was reported as 52.2% in 2014, little is known regarding the practice of family planning among marginalised groups such as the Orang Asli women. This study aims to determine family planning practice among married Orang Asli women in Sepang district and its associated factors. Methods: A cross sectional study using a pretested questionnaire was conducted in five Orang Asli settlements in Sepang using cluster sampling. Chi-square test and simple logistic regression were used in bivariate analysis, where-as binary logistic regression was used to determine the predictors of family planning practice. Results: 212 (58.4%) participants were current users of family planning, with 68.3% of the users reported using oral contraceptive pills. In the logistic regression models, family planning practice was significantly more common among women who had children (AOR= 43.659, 95% CI: 5.788, 329.323), being housewives (AOR=1.973, 95% CI: 1.205, 3.230) and had higher attitude score (AOR=1.113, 95% CI: 1.006, 1.232). Conclusion: The CPR of current study was about the same as the national CPR in 2014. The predictors of family planning practice among Orang Asli women were having children, being a housewife and having a better attitude towards family planning. Future intervention to increase the CPR should focus on improving women’s attitude regarding family planning.